The Importance of Pension Data for Municipal and State Creditor Decisions: Replication and Extensions - Marks, Barry R.; Raman, Krishnamurthy K. (Journal of Accounting Research, 1985)
Barry R. Marks, Krishnamurthy K. Raman, The Importance of Pension Data for Municipal and State Creditor Decisions: Replication and Extensions, Journal of Accounting Research, Vol. 23, No. 2 (Autumn, 1985), pp. 878-886